Optimalisasi Pengelolaan Informasi Data Untuk Peningkatan Kualitas Layanan Di Era Digital - Dery Shadani; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
In the ever-growing digital era, data information management is crucial in ensuring optimal service quality in various sectors. This journal presents an overview of strategies and approaches to optimize data information management to improve service quality in the digital era. The concept of data information management involves the process of collecting, storing, processing and analyzing data to support appropriate decision making. Challenges faced in managing data information in the digital era include large data volumes, technological complexity, data security, and changes in regulations related to privacy. To overcome these challenges, organizations need to implement appropriate strategies, such as investing in advanced technology infrastructure, developing adequate policies and procedures, training to increase data literacy, and implementing effective risk management practices. Technology solutions such as big data analytics, cloud computing, and artificial intelligence (AI) can be utilized to improve data information management. Case studies from various organizations also provide concrete examples of successful implementation of technology strategies and solutions. By utilizing existing information technology, organizations can improve efficiency, accuracy and data accessibility, so they are able to provide better services to users in this digital era.